TYPES OF POTTERY KILNS IN AQUINCUM - Vámos, Péter (Rei Cretariae Romanae Fautorum Acta, 2024)
After the Roman occupation (in the 1st century AD) the shapes of kilns followed the late La-Tène traditions: they were oval or round in plan with tongue-shaped pedestals that supported the grid and divided the combustion chamber in half. These types come to light mostly in the areas where native inhabitants once lived, but can also be found in the territory of the Military Town.